Multistakeholder Collaborative Effort to Enhance Long-Term Follow-Up in the Abdominal Core Health Quality Collaborative. Issue 1 (4th March 2021) - Poulose, Benjamin K.; Schwartzman, Harriet; Huang, Li-Ching; Chouinard, Scott; Coelho, Donald; Macarios, David; Master, Sundeep; Rosen, Michael J.
Abstract : Objective: To determine the effectiveness of a clinical call center in performing focused long-term patient reported outcome (PRO)-based follow-up for ventral hernia patients in routine practice. Background: Long-term follow-up remains the mainstay of assessing quality of care in hernia management. Achieving acceptable rates of long-term follow-up outside of clinical trials in the routine care of patients has been very difficult to achieve. Methods: A prospective quality improvement intervention using a clinical call center in 1000 random patients eligible for long-term (1 year or greater) follow-up after ventral hernia repair in the Abdominal Core Health Quality Collaborative was performed. The primary outcome measure was the proportion of patients with successfully completed PRO-based long-term follow-up. Results: Between 2013 and 2017, the baseline long-term follow-up PRO completion rate was 2167/13, 950 (15.5%). For the Focus on Follow-Up initiative, 890 patients were eligible for contact; a completion rate of 450/890 (50.6%, P < 0.001) was achieved. Conclusions: Clinical call center-based patient contact can greatly facilitate the completion of PROs utilized for long-term follow-up in ventral hernia repair. This has important implications for quality improvement programs and postmarket device surveillance. Abstract : Mini-abstract: In this prospective quality improvement initiative involving 1, 000 patients, we were able to increase patient reported outcome-based long-term follow-up after ventral hernia repair from a baseline rate of 15.5% to 50.6% using a clinical call center. Supplemental Digital Content is available in the text.